Factors Influencing Behavior to Reducing Household Food Waste in Indonesia - Sia Niha, Simon; Lopes Amaral, Maria Augustin; Tisu, Rosadalima (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
The introduction of the determining factor is presumed to be powerful medium to promote a powerful intrusion into household waste management in Indonesia. This study expands the variables theory of planned behavior, the theory of interpersonal characteristics, and a complete model of environmental behavior by using intentions, attitudes, subjective norms, perceived behavioral control, habits, emotions. The sample in this study found 132 people, data processed using SEM Amos version 24. Statistical results and discussion showed that significant factors for behavior to reduce food waste were intentions, habits, attitudes, and perceived behavioral control. And that habits play an essential role in this research, so it is necessary to focus on the importance of the practice to get rid of addictions and be worth emphasizing Keywords: food waste, theory planned behavior, habits